Demographic Dynamics and Agricultural Development in the Coquimbo Region, Chile: A Look at Its Modernization Process (1930-1960) - Briones Molina, Daniel (2025)
The article analyzes the demographic dynamics and the behavior of agricultural activity in the Coquimbo region between 1930 and 1960. During this period, marked by economic modernization in urban areas and industrial growth in Chile, the Coquimbo region exhibited particular characteristics that have not been widely considered in general accounts. The hypothesis suggests that the region experienced slow demographic growth, accompanied by a gradual transition towards urbanization. In this context, Coquimbo developed its own transformation process, which did not align with global trends. This process focused on strengthening agriculture, which became a key activity for regional development by the mid-20th century. Finally, the demographic and productive trends of the region are analyzed, based on national censuses and Agricultural Yearbooks from 1930 to 1960.